IMPLIKASI GOOD GOVERNANCE TERHADAP KINERJA UNIVERSITAS DI SURABAYA - Melvie Paramitha (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
Good corporate governance has long been proclaimed by the government and there are organizations that have become regulators. For good governance at universities or colleges, Minister of Education and Culture Muhammad Nuh started it in 2012. With the good university governance implemented in universities, it can have an impact on the performance of the relevant universities. This study aims to knows the implications of good governance based on the principles of Law No. 12 of 2012 about Higher Education on the performance of universities in Surabaya. The research approach is quantitative research. The number of respondents in the study amounted to 70 people from 7 (seven) universities in Surabaya. Data collection method uses a questionnaire. Statistical testing includes testing validity and reliability and testing hypotheses. Hypothesis testing using multiple linear regression. The results of this study indicate that transparency and non-profit influence the performance of the university. While accountability, quality assurance, and efficiencies do not affect the performance of the university. The results of this study are expected to be a view for regulators in order to clarify mechanisms and measurements for good governance at universities or colleges,